2021
DOI: 10.1111/saje.12284
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Three Countries: What is the Relationship Between COVID‐19, Lockdown and Happiness?

Abstract: The COVID‐19 pandemic led many governments to implement lockdown regulations to curb the spread of the virus. Though lockdowns do minimise the physical damage caused by the virus, there may also be substantial damage to population well‐being. Using a pooled data set, we analyse the relationship between a mandatory lockdown and happiness in three diverse countries: South Africa, New Zealand and Australia. These countries differ amongst others in terms of lockdown regulations and duration. The primary aim is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 25 publications
1
58
0
4
Order By: Relevance
“…Once at least the basic findings from this research are incorporated, it can be concluded that internal marketing communication reaches new dimension of its incorporation into managerial practice. Similarly, Tam et al and Greyling et al have stated the increasing impact of the phenomenon of social psychology in managerial theory and practice and its concepts [47,48].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Once at least the basic findings from this research are incorporated, it can be concluded that internal marketing communication reaches new dimension of its incorporation into managerial practice. Similarly, Tam et al and Greyling et al have stated the increasing impact of the phenomenon of social psychology in managerial theory and practice and its concepts [47,48].…”
Section: Resultsmentioning
confidence: 97%
“…[45,46]. The mechanisms of social psychology are also expected to be slightly changed under the impact of the pandemic [47], as well as the quality and perception of emotions and their importance to the work-life balance concept [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Introduction More and more studies on the pandemic have been done lately as the whole world is currently facing the COVID-19 pandemic, including a study conducted by Talha (2020); Greyling et al (2020); Brooks et al (2020); Jiao et al (2020); Orgilés et al (2021); Sahid et al (2020); Li et al (2020). Preventive measures such as the implementation of movement control orders that limit various social activities have led to changes in the daily lifestyle of the community compared to the previous life (Talha, 2020).…”
Section: Methods Of Overcoming Parental Psychological Stress In Children's Education During the Period Of Movement Control Order (Mco)mentioning
confidence: 99%
“…Preventive measures such as the implementation of movement control orders that limit various social activities have led to changes in the daily lifestyle of the community compared to the previous life (Talha, 2020). This is not only the case in Malaysia but also experienced by the entire world population with the enforcement of curfews (lockdown) to control the spread of the COVID-19 virus (Greyling et al, 2020). From the point of view of community safety, this enforcement is recognized as an excellent preventive measure but has side effects that exist behind these social restrictions imposed on individuals, families, and society.…”
Section: Methods Of Overcoming Parental Psychological Stress In Children's Education During the Period Of Movement Control Order (Mco)mentioning
confidence: 99%
“…Greyling et al ( 2021a ) and Rossouw et al ( 2021 ) conducted two studies that used the GNH index to investigate the determinants of happiness before and during the first months of the government-imposed lockdown in South Africa. In a third study, Greyling et al ( 2021b ) focused on using the GNH to investigate the relationship between the stringency of lockdowns and happiness in a cross-country study that focused on South Africa, New Zealand and Australia. None of these GNH studies followed the wellbeing dynamics of a nation on a day-to-day basis in order to understand the relationship between the number of daily COVID-19 cases, national wellbeing and emotions from before and during the passage of the pandemic or whether changes in the number of COVID-19 cases led or lagged national wellbeing.…”
Section: Big Data and The Gross National Happiness Indexmentioning
confidence: 99%